STRATEGI SEKOLAH DALAM MENERAPKAN SISTEM MANAJEMEN MUTU (SMM) BERBASIS ISO 9001:2015 - Antonius Widi Nugroho (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2017)
This study aims to describe the application of Quality Management System (SMM) based on ISO 9001: 2015 in SMAK St. Albertus Malang. This research method using descriptive qualitative approach with research location at SMAK St. Albertus Malang. SMAK St. Albertus Malang has implemented the SMM ISO 9001: 2015 mainly on management responsibilities consisting of management commitment, customer focus, quality policy, management planning, responsibility, authority and communication and management review well. However, the implementation has not been maximized and has not referred to IWA-2 as a reference for the implementation of SMM ISO 9001: 2015 in educational institutions for more effective implementation and can meet the needs and expectations of stakeholders. DOI: https://doi.org/10.17977/um025v1i32017p227